The Influence of Brand Experience, Brand Trust, and Perceived Value on Brand Loyalty of Maybelline Products in Surabaya - Astutik, Retno Dwi; Purwanto, Sugeng (PT FORMOSA CENDEKIA GLOBAL, 2024)
The current era of technological advancement has significantly changed various aspects of human life, including behavior patterns and lifestyles. Lifestyle changes that were initially cosmetic and used only on special occasions have now become daily necessities, leading to diverse demands for cosmetics and intense competition. This situation presents both opportunities and challenges for cosmetic companies. This study aims to determine how brand experience, brand trust, and perceived value affect brand loyalty of Maybelline products in Surabaya.The research method employed is quantitative research, with a sample size of 102 respondents who filled the sample criteria. Sampling was conducted using the Purposive Sampling technique, with the criteria being female, Maybelline product user, having made at least two purchases, and residing in Surabaya. Data analysis in this study utilized SEM-PLS. The results indicate that Brand Experience, Trust, and Perceived Value positively influence Brand Loyalty towards Maybelline products in Surabaya. The research method employed is quantitative research, with a sample size of 102 respondents who filled the sample criteria. Sampling was conducted using the Purposive Sampling technique, with the criteria being female, Maybelline product user, having made at least two purchases, and residing in Surabaya. Data analysis in this study utilized SEM-PLS. The results indicate that Brand Experience, Trust, and Perceived Value positively influence Brand Loyalty towards Maybelline products in Surabaya.